Comparing some physical and inorganic parameters of raw and treated river water in Selangor and Kuala Lumpur - Lim, P.S.; Ibrahim, S.; Mohd, H.; Mohammad, A.S. (Malaysian Water Association, 2004)
The levels of pH, turbidity, colour, ammonia, chlorine, and heavy metals have been measured for raw and treated water from the Ampang Intake, Bukit Nanas, Wangsa Maju, Batu River, Cheras 11th Mile and Langat River water treatment plants (WTPs). The results matched the trend observed by the Departments of Health over the year of study. Although the water quality at all WTPs met the requirements of the Departments of Health Malaysia, water from the Langat River catchment area, particularly Cheras 11th Mile contained significantly higher levels of contaminant compared to the other WTPs. This has been attributed to relatively higher levels of waste discharge from domestic, industrial and land filling activities in the vicinity of the Langat River catchment area.